Об эффективности кинематических методов определения состава рассеянных звездных скоплений с малыми собственными движениями - Лазоренко, Г.А.; Лазоренко, П.Ф. (Кинематика и физика небесных тел, 1991)
С помощью моделирования реальных распределений звезд в окрестностях рассеянных скоплений выполнен анализ ошибок, свойственных известным кинематическим методам. Показано, что в зависимости от метода и характеристик распределения звезд при отборе может теряться 10—60 % общего числа звезд скопления n и ошибочно включаться в состав скопления от 0.1 n до 2 n звезд фона. Наименьшими ошибками (соответственно 10—40 % и 0.1 n—0.2 n) отличается кинематический метод, в котором учитывается распределение звезд в пространстве и по видимому блеску V или V₀. При идентификации ярких звезд этот метод позволяет уменьшить ошибки отбора в 1.5— 3 раза по сравнению с другими обычно применяемыми методами. The membership determination errors, inherent in some-known kinematic methods, used for separation of field stars and cluster members, are discussed. An error analysis have been carried out by means of simulation of real star distribution in the vicinity of two open clusters — their proper motions, angular coordinates and visual magnitudes. It has been shown that, depending on the method applied and on characteristics of star distribution, the separation can lead to losses of up to Sc = 10—60 % of the total number of cluster members n. Simultaneously up to Sф = 0.1n— 2n field stars can be erroneously included in the list of cluster members. A method allowing both for kinematic data and visual magnitudes V or Vo distribution has minimum errors Sс = (O.1—0.4)n, Sф = (0.1—0.2)n, and is especially suitable for identification of bright stars. For clusters with small proper motions none of the known methods allows to obtain reliable lists of members on the error level of Sc+Сф < O.1n.